Kewirausahaan Berbasis Pendidikan Karakter di Dayah Ummul Ayman, Samalanga - Lukman Lukman; M Nazaruddin; Saifuddin Yunus (Jurnal Sosiologi Agama Indonesia (JSAI), 2021)
This study is aimed to find out how the empowerment strategy of entrepreneurship is carried out at Dayah Ummul Ayman, Sub-District of Samalanga, District of Bireuen. This study uses descriptive qualitative research method. Informants in this study consisted of Tgk. Nuruzzahri Yahya, Head of Dayah Ummul Ayman, ustaz and students, including some members of the community. Data collection techniques were carried out through observation, interviews and document studies. Based on the result of the study shows that the empowerment strategy of entrepreneurship based on education character can encourage student interest and motivation at Dayah Ummul Ayman. The final conclusion shows that through the empowerment of entrepreneurial activities based on character education enriched with religious values can encourage the interest and motivation of students in entrepreneurship activities.